The Cost of Prospective Memory in Children: The Role of Cue Focality - Cejudo, Ana B.; Gómez-Ariza, Carlos J.; Bajo, M. Teresa (Frontiers in Psychology, 2019)
Prospective memory (PM) is an essential ability in daily life, since it involves remembering to perform an intention. While PM largely develops during childhood and adolescence, its underlying mechanisms are still poorly understood. In general, age differences in PM have been found with tasks in which the prospective cues are not part of the ongoing activity (non-focal PM tasks). In the present study, we evaluated the cognitive cost produced by a PM task over the ongoing activity by comparing the performance of a single condition with that of an ongoing activity condition involving a prospective intention. Specifically, to determine the impact of cue focality on performance as a function of age, we tested two groups of children (6 and 11 years old) in three experimental conditions: single, focal and non-focal prospective cues. In the single condition, children were only asked to perform the ongoing task (to categorize images as animal or non-animal). In the focal condition, in addition to performing the ongoing activity, participants were asked to press different keys whenever the image appearing on the screen was a kite or a ball. In the non-focal condition, children were to press the keys if the color of the frame of the screen changed to magenta or grey. Although reaction times were greater for the non-focal conditions in both age groups, the results showed worse performance on the ongoing activity for both the focal and the non-focal conditions (relative to the single condition) in the younger children. This difference was less pronounced in older children so that response times for focal and non-focal cues differed from the single condition, but the difference in performance between focal and single conditions was not reliable. These findings, which are partly in line with the dual process framework (McDaniel, Umanath, Einstein, & Waldum, 2015), suggest that while non-focal prospective cues compromise attentional control in younger and older children, focal cues seem to rely on less effortful processes in older children.